Pilotstudie zu prosodischen Strategien in frei gesprochenen Konferenzvorträgen deutscher Linguisten - Marta Rogozińska (Beiträge zur Allgemeinen und Vergleichenden Sprachwissenschaft)
In this article, partial results of an empirical pilot study on prosodic strategies are presented in freely spoken conference presentations by German linguists. The study aims to take a closer look at the coexistence of prosodic and pragmatic phenomena in scientific discourse and to document the first observations on the speaking behavior of scientists in the field of prosody. The subject of investigation is three selected expert lectures, which were recorded as part of the GeWiss project at international conferences in Germany. The basis of the investigation is the auditory analysis carried out by the author, which is additionally supplemented by acoustic information in Praat.